Improving the mix of institutional and community care for older people with dementia: an application of the balance of care approach in eight European countries. (1st December 2016) - Tucker, S.; Sutcliffe, C.; Bowns, I.; Challis, D.; Saks, K.; Verbeek, H.; Cabrera, E.; Karlsson, S.; Leino-Kilpi, H.; Meyer, G.; Soto, M.E.; ,
Abstract : Objectives : To examine whether the mix of community and institutional long-term care (ILTC) for people with dementia (PwD) in Europe could be improved; assess the economic consequences of providing alternative services for particular groups of ILTC entrants and explore the transnational application of the 'Balance of Care' (BoC) approach. Method: A BoC study was undertaken in Estonia, Finland, France, Germany, the Netherlands, Spain, Sweden, and the UK as part of the RightTimePlaceCare project. Drawing on information about 2014 PwD on the margins of ILTC admission, this strategic planning framework identified people whose needs could be met in more than one setting, and compared the relative costs of the possible alternatives. Results: The findings suggest a noteworthy minority of ILTC entrants could be more appropriately supported in the community if enhanced services were available. This would not necessarily require innovative services, but more standard care (including personal and day care), assuming quality was ensured. Potential cost savings were identified in all countries, but community care was not always cheaper than ILTC and the ability to release resources varied between nations. Conclusions : This is believed to be the first transnational application of the BoC approach, and demonstrates its potential to provide a consistent approach to planning across different health and social care systems. Better comparative information is needed on the number of ILTC entrants with dementia, unit costs and outcomes. Nevertheless, the findings offer important evidence on the appropriateness of current provision, and the opportunity to learn from different countries' experience.